2014
DOI: 10.1007/s13204-014-0361-y
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of enrofloxacin SLNs and its pharmacokinetics in emu (Dromaius novaehollandiae) birds

Abstract: The study was conducted to formulate the enrofloxacin solid lipid nanoparticles (SLNs) with sustained release profile and improved pharmacological activity and evaluate the pharmacokinetic behaviour of enrofloxacin SLNs after oral routes of administration in emus. The SLNs were prepared using tripalmitin as lipid carrier, Tween 80 and Span 80 as surfactants and polyvinyl alcohol (PVA) as a stabilizer by a hot homogenization coupled with ultrasonication method. The prepared enrofloxacin SLNs formulations were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In this study, the value of diffusion exponent ( n ) in the Korsmeyer–Peppas model was lower than 0.45, which indicated the drug release from NPs follows the behavior of Fickian diffusion. , Initial burst release of ENRO from PLGA­(ENRO)­NPs in the first few hours could be due to dissolution of the drug loaded in the NPs, which follows the Fickian diffusion. After which, low and sustained release of ENRO from the NPs can be attributed to the polymer erosion/degradation over time. , It has been reported that the diffusion of free ENRO is about 94% in first 2 h and 100% diffusion is observed within 24 h . This report of free ENRO shows that PLGA­(ENRO) NPs have sustained release over the period of 4 days.…”
Section: Resultsmentioning
confidence: 75%
“…In this study, the value of diffusion exponent ( n ) in the Korsmeyer–Peppas model was lower than 0.45, which indicated the drug release from NPs follows the behavior of Fickian diffusion. , Initial burst release of ENRO from PLGA­(ENRO)­NPs in the first few hours could be due to dissolution of the drug loaded in the NPs, which follows the Fickian diffusion. After which, low and sustained release of ENRO from the NPs can be attributed to the polymer erosion/degradation over time. , It has been reported that the diffusion of free ENRO is about 94% in first 2 h and 100% diffusion is observed within 24 h . This report of free ENRO shows that PLGA­(ENRO) NPs have sustained release over the period of 4 days.…”
Section: Resultsmentioning
confidence: 75%
“…Generally, formulations with zeta potential greater than +25 mV and lower than −25 mV are considered stable due to electrostatic repulsion between the particles, since lower zeta potential may cause aggregation of the particles through van der Waal interactions. 47 Particle size in the range of 238 ± 12.13 to 319 ± 12.47 nm and % encapsulation efficiency (% EE) in the range of 28 ± 4.24 to 46.5 ± 6.19 were obtained in the designed nine formulations. It was suggested by the software that quadratic model was best fitted for all the responses studied.…”
Section: Resultsmentioning
confidence: 89%
“…It is biodegradable and used to treat infection of urinary tract, skin and respiratory. Moreover, it has antibacterial activity against gram-positive and gram-negative bacteria [7,8]. This research has an idea to modify chitosan with enrofloxacin for increase antibacterial efficacy.…”
Section: Introductionmentioning
confidence: 99%